Assessing the mother tongue-based multilingual education policy in the Philippine mathematics education - Katherine Therese Salonga Tungul; Minie Rose Lapinid (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
The Philippine Department of Education developed and has been implementing the Mother Tongue-Based Multilingual Education (MTB-MLE) policy in response to encouraging findings from earlier research studies on using the mother tongue in early education. The purpose of this study is to evaluate how the MTB-MLE Policy is being implemented in terms of classroom instruction, teacher and school readiness, and student proficiency in their mother tongue, Kapampangan, and mathematics in the first five years of implementation in the Sasmuan District of Pampanga, Philippines, using an explanatory sequential mixed-methods research design. Teachers rated the implementation of the MTB-MLE policy positively but experienced some difficulties. Data analysis from interviews with teachers, school heads, district supervisors, and class observations revealed some issues, concerns, coping strategies, and best practices. The results of the two achievement exams students took were satisfactory, providing evidence of the value of using their native tongues in the classroom amidst challenges. Implications of the results were drawn for further improvement in the practice of the MTB-MLE policy in Mathematics Education.